Effect of polystyrene nanoplastics on cell apoptosis, glucose metabolism, and antibacterial immunity of Eriocheir sinensis. (15th October 2022) - Nan, Xingyu; Jin, Xingkun; Song, Yu; Zhou, Kaimin; Qin, Yukai; Wang, Qun; Li, Weiwei
Abstract: The adverse effects of plastic waste and nanoplastics on the water environment have become a focus of global attention in recent years. In the present study, using adult Chinese mitten crabs ( Eriocheir sinensis ) as an animal model, the bioaccumulation and the in vivo and in vitro toxicity of polystyrene nanoplastics (PS NPs), alone or in combination with the bacteria, were investigated. This study aimed to investigate the effects of PS NPs on apoptosis and glucose metabolism in Chinese mitten crabs, and whether PS NPs could synergistically affect the antibacterial immunity of crabs. We observed that NPs were endocytosed by hemocytes, which are immune cells in crustaceans and are involved in innate immunity. The RNA sequencing data showed that after hemocytes endocytosed NPs, apoptosis and glucose metabolism-related gene expression was significantly induced, resulting in abnormal cell apoptosis and a glucose metabolism disorder. In addition, exposure to NPs resulted in changes in the antimicrobial immunity of crabs, including changes in antimicrobial peptide expression, survival, and bacterial clearance. In summary, NPs could be endocytosed by crab hemocytes, which adversely affected the cell apoptosis, glucose metabolism, and antibacterial immunity of Eriocheir sinensis . This study revealed the effects of NPs on crab immunity and lays the foundation for further exploration of the synergistic effect of NPs and bacteria. Graphical abstract: Image 1 Highlights: Polystyrene nanoplastic can enter the hemolymph and be endocytosed by hemocytes. Polystyrene nanoplastic exposure could exacerbate apoptosis in crab hemocytes. Polystyrene nanoplastic exposure induced glucose metabolism disorder. Polystyrene nanoplastics have negative effects on antibacterial immunity of crab.